Perioperative red blood cell transfusion in orofacial surgery - Park, So-Young (J Dent Anesth Pain Med, 2017)
In the field of orofacial surgery, a red blood cell transfusion (RBCT) is occasionally required during double jaw and oral cancer surgery. However, the question remains whether the effect of RBCT during the perioperative period is beneficial or harmful. The answer to this question remains challenging. In the field of orofacial surgery, transfusion is performed for the purpose of oxygen transfer to hypoxic tissues and plasma volume expansion when there is bleeding. However, there are various risks, such as infectious complications (viral and bacterial), transfusion-related acute lung injury, ABO and non-ABO associated hemolytic transfusion reactions, febrile non-hemolytic transfusion reactions, transfusion associated graft-versus-host disease, transfusion associated circulatory overload, and hypersensitivity transfusion reaction including anaphylaxis and transfusion-related immune-modulation. Many studies and guidelines have suggested RBCT is considered when hemoglobin levels recorded are 7 g/dL for general patients and 8-9 g/dL for patients with cardiovascular disease or hemodynamically unstable patients. However, RBCT is occasionally an essential treatment during surgeries and it is often required in emergency cases. We need to comprehensively consider postoperative bleeding, different clinical situations, the level of intra- and postoperative patient monitoring, and various problems that may arise from a transfusion, in the perspective of patient safety. Since orofacial surgery has an especially high risk of bleeding due to the complex structures involved and the extensive vascular distribution, measures to prevent bleeding should be taken and the conditions for a transfusion should be optimized and appropriate in order to promote patient safety.